Pengaruh Kualitas Sdm, Beban Kerja Dan Komunikasi Terhadap Loyalitas Di Kecamatan Tarumajaya Bekasi Utara - PutriMutia; Ery Teguh; Fahmi Sahlan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine the influence of human resource quality, workload and communication on employee loyalty in Tarumajaya District, Bekasi Regency. The objects of this research are employees in Tarumajaya District, Bekasi Regency. This research uses a quantitative approach with multiple linear regression analysis, to test and prove the research hypothesis using the SPSS version 22 application. The population in this research is employees of Tarumajaya District, Bekasi Regency, totaling 53 respondents. Research shows that HR Quality, Workload and Communication together have a positive and significant effect on Employee Loyalty. By testing the coefficient of determination, a value of 0.838 was obtained, which means 83.8%. The Employee Loyalty variable can be explained by the HR Quality, Workload and Communication variables while the remaining 16.2% is explained by other variables